2nd International Conference for Innovation in Biomedical Engineering and Life Sciences ICIBEL 2017 (in conjunction with APCMBE 2017),10 - 13 December 2017, Penang, Malaysia (IFMBE Proceedings,, 2018)
This volume presents the proceedings of ICIBEL 2017, organized by the Centre for Innovation in Medical Engineering (CIME) under Innovative Technology Research Cluster, University of Malaya. It was held in George Town, Penang, Malaysia, from 10-13 December 2017. The ICIBEL 2017 conference promotes the latest research and developments related to the integration of the Engineering technology in medical fields and life sciences. This includes the latest innovations, research trends and concerns, challenges and adopted solution in the field of medical engineering and life sciences.